Deteksi Gizi Buruk Pada Balita Menggunakan Metode Fuzzy Logic (Studi Kasus Puskesmas Kecamatan Semidang Alas Kabupaten Seluma) - Yuza Reswan; Yulia Darnita; A.R Walad Mahfuzhi; Yonaldo Putra (Jurnal Media Infotama, 2024)
Nutrition plays a crucial role in maintaining health and well-being throughout the life cycle, especially in toddlers. Malnutrition can affect the physical growth, intelligence, and productivity of children. Factors such as economic conditions, parental attention, and unsupportive environments can contribute to cases of malnutrition in toddlers. Suboptimal monitoring of toddler development can increase the prevalence of malnutrition cases. This research aims to develop a Fuzzy Logic-based Decision Support System (DSS) application to detect malnutrition in toddlers, with a focus on the Semidang Alas Community Health Center in Seluma Regency. This study discusses variables for assessing malnutrition in toddlers, applies the Fuzzy Logic method to detect these conditions, and designs an application to diagnose malnutrition in toddlers. The research also includes community education on weight changes in malnourished toddlers and general nutritional status, providing input to improve services for malnourished toddlers. Assessment criteria involve the child's weight, height, and age, using Fuzzy Logic and DSS Application for data processing. Information handling related to malnutrition is limited to visible symptoms. Software development focuses on recognizing malnutrition diagnoses in children aged 0-5 years. A case study was conducted at the Semidang Alas Community Health Center using direct observation, nurse/midwife interviews, questionnaires, and literature reviews. System needs analysis used the Fuzzy Sugeno method. The malnutrition detection application was successfully built using Fuzzy Logic, providing detection results based on age, weight, and height. The defuzzification process produced detection values as a reference for further treatment. Application development involved both display and data aspects, with testing conducted with relevant parties to ensure the accuracy of detection results. User criticisms and suggestions provided valuable input for the improvement and development of this application.